2012
DOI: 10.17221/5854-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive study of botulism in an Austrian dairy herd: a case report

Abstract: An outbreak of botulism was suspected at an Austrian dairy farm in June 2010. Six Simmental cows, out of a herd of 29, were affected and showed the typical signs. The affected cows included either animals suffering from sudden recumbency and reduced tongue tone or others which developed paresis, which gradually led to recumbency. Most of the affected animals died. Two cases were submitted to the Clinic for Ruminants at the University of Veterinary Medicine Vienna in order to clarify the cause of illness. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Most of the cattle outbreaks reported in the literature are dairy cattle [8,[10][11][12]14,[20][21][22][23][24][25]. This outbreak emphasizes that beef cattle can also be affected by botulism, even in small farms and not only in feedlots [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the cattle outbreaks reported in the literature are dairy cattle [8,[10][11][12]14,[20][21][22][23][24][25]. This outbreak emphasizes that beef cattle can also be affected by botulism, even in small farms and not only in feedlots [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…They are, however, commonly encountered in Australia and South Africa, where bovine and avian husbandry are mixed [29]. Several type C outbreaks of bovine botulism due to contamination of feed with a carcass, especially a cat carcass, have been reported in the literature [8,14,[21][22][23][24]30,31]. Contaminated hay or silage was involved each time.…”
Section: Discussionmentioning
confidence: 99%
“…Death or salvage for slaughter was the sequel after calcium borogluconate administration in cattle suspected for botulism [ 18 ]. Some authors have reported recovery of cows from botulism after 1 week [ 19 , 20 ]. In this study, 17 animals recovered over a period of 2-30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Kummel et al . (2012) reported maintenance of pregnancy and recovery from botulism in a cow [ 20 ]. Despite contradicting the recommendations of intravenous fluid administration by earlier researchers, symptomatic management adopted in this study aided the recovery from botulism [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The disease is more evident in children under one year of age because there is more chance to germinate spore in the gastro-intestinal tract (GIT) and so productions of more exotoxins [2]. species of C. botulinum are classified in I to IV subgroups, from which, the I and II groups (A, B, E, F) and B, C and D were respectively identified in human and cattle [2,3,4,5]. The groups of bacteria are phenotypically dissimilar, for instances, the biochemical characteristics and production of metabolites in different types of the bacteria are not appropriate enough to differentiate them [6].…”
Section: Introductionmentioning
confidence: 99%